DOZ047.39: Respiratory morbidity at the age of one year in children with esophageal atresia: data from the French National Esophageal Atresia Register. (24th June 2019) - Lejeune, S; Rousseau, V; Bonnard, A; Michaud, L; Gelas, T; Boubnova, J; Jacquier, C; Irtan, S; Breton, A; Fouquet, V; Guinot, A; Lamireau, T; et al.
Abstract : Summary: Respiratory diseases are common in children with esophageal atresia (EA), leading to an increased morbidity and mortality in the first months of life. Objective: Assess the prevalence of hospitalizations linked to a respiratory disease and of maintenance inhaled therapy at the age of 1 year in French children. Methods: Population based-study using data from the French national EA register. We included all children born between 2010 and 2015 with data available at birth and at follow-up at one year of age. Results: A total of 981 patients born with EA were included in the register, 75 of them (8%) being deceased at the age of 1 year. Data were missing for 60 patients, thus 846 children (86%) were retained for analysis. EAs were type III of Ladd classification in 89% and type I in 7%. Rate of prematurity was 37% while 51% presented associated malformations. At 1 year of age, 1297 hospitalizations were reported for 508 patients (60%), at least one hospitalization for a respiratory disease for 251 children (51%). Factors significantly associated with respiratory hospitalizations were longer median length of oxygen supplementation ( P  < 10 −2 ) and noninvasive ventilation in the neonatal period ( P  = 0.02), gastrostomy tube ( P  < 10 −2 ), esophageal anastomosis dilation ( P  < 10 −2 ). At 1 year of age, 29% had an inhaled maintenance treatment, and 85% inhaled corticosteroids. Factors significantly associated with inhaled maintenance treatment were male gender ( P  = 0.04), advanced older median age at gastrostomy tube insertion ( P  < 10 −3 ), enteral feeding at one year of age ( P  < 10 −3 ). Conclusion: This study shows a high rate of respiratory problems responsive of frequent hospitalizations and inhaled maintenance treatment in children born with EA in the first year of life.